PENINGKATAN KOMPETENSI CLOUD ACCOUNTING SISWA SMKN 1 DUMAI MELALUI PELATIHAN ZAHIR ACCOUNTING VERSI ONLINE - Heri Ribut Yuliantoro; Hamdani Arifulsyah; Tobi Arfan; Fifitri Ali; Meliza Putriyanti Zifi (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Knowledge of the operation of the Online version of Zahir Accounting as one of the Cloud Accounting applications is very important, especially for Vocational High School (SMK) students. As graduates who are ready to work, expertise in operating the Online version of Zahir Accounting must be possessed by SMK graduates because currently many companies are using the application. This community service activity is carried out in the form of offline training on Zahir Accounting for students of the Accounting and Institutional Finance Department at SMKN 1 Dumai. Currently, students of SMKN 1 Dumai have never received training on the operation of the Online version of Zahir Accounting. Basically, this training activity aims to provide knowledge and skills to SMKN 1 Dumai students about the use of the Online version of Zahir Accounting Software so that it can be a way to increase student competence, especially in terms of Cloud Accounting technology. This training was attended by 20 students of SMKN 1 Dumai majoring in Accounting and Institutional Finance. The results of the review of this training show that in general the participants' satisfaction related to the implementation of the training is very good, and in general the participants understand the training material well. It is hoped that the Online version of Zahir Accounting will become one of the students' teaching materials related to accounting and financial management with cloud accounting technology.